Implementación SAP R/3 PSP Brasil - Yamauchi Oyama, Eduardo Mitsuo (2018)
Family business with more than 60 years, dedicated mainly to the preparation, distribution and marketing of pasta, with a high growth rate in recent years, recently acquired by a transnational company. Being one of the main strategies of the corporation to have the same technological platform in all its headquarters, is how the project described in this report is born. For the execution of the same, it was necessary a year and a half that includes from the planning at management level to the Go-live stage. The budget was approximately $ 5 million with the participation of a team of 50 people including project managers from the companies involved, corporate directors, key users from both countries and the entire consultative team from Peru and Brazil.